Cultural Experience, Possible Selves and Subjective Well-Being Among Anishnaabe Youth - Trull, Graham G. (University of Windsor, 2013)
Aboriginal youth in Canada face a number of economic, health and social challenges, while being one of the fastest-growing segments of the country's population. Researchers have suggested that involvement in positive cultural experiences can be beneficial to the well-being of these youth. However, past research has not defined the types of cultural experience that are most impactful, or the areas of well-being that are affected. As well, no research has investigated the role that cultural experience may have on the views of the future among Aboriginal youth, or how these views may impact well-being. Working together with Walpole Island First Nation community members, a research survey was created for youth in the community. Researchers tested whether each of three types of subjective well-being (SWB; positive affect, negative affect, life satisfaction) would be predicted by the linear combinations of cultural experience variables (cultural identity, acculturation, bicultural identity integration) and/or variables relating to future possible selves (planning and likelihood), while controlling for baseline variables typically predictive of SWB (finances, social support, health). The relationship between cultural experience and possible selves was also investigated. Participants were 132 Anishnaabe youth ages 15-25 (63 male, 69 female) who were members of or resided in Walpole Island First Nation. Results showed that cultural experience and possible selves variables were predictive of positive affect. However, cultural experience and possible selves were not significantly predictive of negative affect or life satisfaction. Significant relationships were also found between cultural experience variables and possible selves planning and likelihood. Additional analyses were completed by the researchers to clarify individual relationships between these variables. Theoretical and community implications are discussed.